Children With Inflammatory Bowel Disease in the COVID-19 Main Endemic Focus: The Lombardy Experience - Sansotta, Naire; Norsa, Lorenzo; Zuin, Giovanna; Panceri, Roberto; Dilillo, Dario; Pozzi, Elena; Giacomo, Costantino De; Moretti, Chiara; Celano, Rosaria; Nuti, Federica; Sgaramella, Paola; Stefano, Marina Di; et al. (Frontiers in Pediatrics, 2021)
Objectives: In the era of Coronavirus 2019 (COVID-19), concern has been raised for immunosuppressed patients, including children with inflammatory bowel diseases (IBD). We aimed to collect data from IBD tertiary centers of Lombardy during pandemic. Methods: A cross-sectional survey enrolling IBD children has been completed by seven major IBD centers in Lombardy during lockdown. The clinical form included questions on any symptom consistent with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the IBD adherence treatment. Furthermore, we have reviewed all IBD medical records including new IBD diagnoses and flares in known IBD patients after the lockdown. Results: Questionnaires of 290 IBD children were returned during lockdown. Out of them, 24 children (8%) complained of mild symptoms suspicious of SARS-CoV-2 infection without needing hospitalization or changing IBD treatment. During the lockdown, one patient presented with IBD flare and one had infectious colitis, with no new IBD cases. Conversely, after lockdown, 12/290 (4%) children relapsed and 15 children were newly diagnosed with IBD. Last year, in the same timeframe, 20/300 (7%) children presented with IBD flare, while 17 children had IBD onset with no statistical difference. Conclusions: Our data on children with IBD in a high COVID-19 prevalence region are reassuring. Only a minority of IBD children had mild symptoms, and no hospitalization or treatment modification was needed. Standard IBD treatments including biologics were safely continued. New IBD diagnoses and flares in known IBD children occurred after the lockdown phase, although no significant difference was found compared with the previous year.